Ensino de História na Amazônia – inserção da história e cultura dos povos indígenas na Licenciatura de História da UFRR: The Teaching Of History In Amazônia – Introduction Of History And Culture Of The Indigenous In Licentiate Of History Of Ufrr (Revista Cocar, 2023)
Este texto discute a construção de um ensino de história que insira a história e a cultura dos indígenas da Amazônia como conteúdo dos componentes curriculares. Apresenta como este tema fez parte do currículo dos cursos de licenciatura antes da Lei 11.645 e como há uma demanda para que passe a fazê-lo. Inter-relacionar isso com a construção da legislação que se constrói no Brasil a partir da legislação dos anos 1990 e, ainda, como aparece na reformulação do currículo do Curso de História da UFRR. Assim, os objetivos são: problematizar a inserção dos conteúdos da história e da cultura das etnias indígenas de Roraima nos componentes curriculares do curso de História, considerando nossa inserção no contexto amazônico; produzir uma articulação com a Lei 11.645 na formação dos professores de história; e fazer uso do aprendizado no Núcleo Docente Estruturante do Curso de História da UFRR. Como metodologia utilizou-se a análise bibliográfica e análise documental, privilegiando as legislações e o PPC do curso de História.Palavras-chave: Ensino de História; História Indígena; Lei 11.645/08. Abstract This text aims to discuss the construction of a Teaching of History that inserts the history and culture of the indigenous people from Amazônia as content of the curricular components. To do so, it will be necessary to present how this theme was a part of the curriculum of licentiate courses before Law 11.645/08 and how there is a demand to start doing so. Interrelate this with the construction of the legislation that was built in Brazil from 1990 onwards (PCNs, Resolution, DCNs, LDBEN until Law 11.645/08) and, also, as it shows up in the reformulation of the curriculum of the History course at UFRR, that happened in 2022. Therefore, the objectives of this articles are: to problematize the insertion of contents about History and Culture of indigenous ethnicities of Roraima in the curricular components in the Licentiate course of History, considering our insertion in the Amazônia context; create a reflexive articulation with the legislation put into effect, notably the law 11.645/08 before what impacts on the formation of History teachers; and, finally, according to our experience, as an empirical subsidy, to make use of learning in the Structuring Teacher Nucleus/NDE of the Licentiate course when reformulating the PPC of the History course at UFRR. As a methodology, bibliographic analysis and document analysis were used, favoring the laws and the PPC of the History course.Keywords: History teaching, Indigenous history, Law 11.645/08, NDE.